Identifying Concepts of Physical Activity Which Are Clinically Meaningful to Patients and Care Providers: A Systematic Review of Qualitative Research - Candice Taguibao; Salma Ajraoui; Jake Centra; Kieran F. Reid; Christina Daskalopoulou; Alberto Conde Freniche; Alan L. Hamilton; Astrid M. H. Horstman; Benjamin X. Collins; Jessilyn Dunn; Elena S. Izmailova (Clinical and Translational Science)
ABSTRACT Physical activity (PA) is indispensable for overall health. Sub‐optimal PA is linked to reduced quality of life (QOL) and premature death. In clinical research and therapeutics development, defining aspects of PA that are meaningful to patients and care providers is essential for designing tailored interventions, identifying individual contextual factors, and enhancing patient satisfaction and engagement in their own well‐being. As digital health technologies (DHTs) measuring PA rapidly evolve, there is an opportunity to further define concepts. A systematic review of qualitative studies to identify concepts of PA that are meaningful to patients and care providers was conducted. Conditions covered included Parkinson's disease, multiple sclerosis, chronic obstructive pulmonary disease, cancer, Duchenne muscular dystrophy, chronic heart failure, sickle cell disease, osteoarthritis, and sarcopenia. We analyzed studies published in the last 20 years utilizing qualitative or mixed methods techniques to describe aspects of PA that patients want to prevent from worsening or improve. Among the 5228 articles returned, 105 studies were included. Thematic synthesis revealed five meaningful aspects of health (MAH) related to PA: ambulation‐dependent activities, balance‐dependent activities, activities needing upper limb function, changing body positions, and participating in activities of different intensities. Patients also reported PA as important to QOL and influenced by internal and external facilitators and barriers. This research presents new findings related to PA MAHs across various therapeutic areas, which go beyond walking. The findings provide a foundation for defining concepts of interest, measures, and endpoints, with applications in clinical research and care, including patient‐focused development of digitally derived measures.